Tamoxifen blocks chloride channels. A possible mechanism for cataract formation. - Zhang, J J (1994)
Tamoxifen is an antiestrogen frequently used in the treatment of breast cancer and is currently being assessed as a prophylactic for those at high risk of developing tumors. We have found that tamoxifen and its derivatives are high-affinity blockers of specific chloride channels. This blockade appears to be independent of the interaction of tamoxifen with the estrogen receptor and therefore reflects an alternative cellular target. One of the clinical side effects of tamoxifen is impaired vision and cataract. Chloride channels in the lens of the eye were shown to be essential for maintaining normal lens hydration and transmittance. These channels were blocked by tamoxifen and, in organ culture, tamoxifen led to lens opacity associated with cataracts at clinically relevant concentrations. These data suggest a molecular mechanism by which tamoxifen can cause cataract formation and have implications for the clinical use of tamoxifen and related antiestrogens.